NAGA NATIONALISM: THE CROSSROAD - Ngullie, Tumben (International Journal of Research -GRANTHAALAYAH, 2024)
This paper is an attempt to explore and look into Nationalism in the context of Nagaland which offers a unique historical background in so far as any discussion on the idea of nation is concerned. Taking into account the pre-British intrusion from 1932 and the opening of a critical chapter from 1947 onwards, Nagaland was historically outside the pale of the great Indian civilization. Year after Indian independence, Nagas fell under the spell of this great nation and the holocaust continues several decades which witnessed different political pathways within. From its nascent stage in 1918 with the formation of the Naga Club and the birth of Naga National Council (NNC) in 1945 to the signing of the historic Naga Peace Accord in 2015, the Naga political movement have been a complex issue projecting the nexus of policy makers, stakeholders and national workers who operates by exploiting the Naga issue rather than solving it. This paper presents the critical endeavour to situate the Naga political movement in the present context and attempts to understand and reimagine the relevance of Naga nationalism in the light of its expectations respecting its unique history.